Computação móvel aplicada como sistema de supervisão de processos de manufatura industrial - Schuch, Rafael (Universidade do Vale do Rio dos Sinos, 2013)
The objective of this paper is to present a solution developed with mobile computing resources to control the manufacturing process industry, following the availability and efficiency of machines in a production line manufacturing. The method adopted the literature for the presentation of concepts related to our research and contextualization of the problem and solution. A functional prototype developed on the Windows Phone platform was developed in order to propose a solution to the problem proposed. Finally, it is concluded that the application of mobile computing as a resource for remote monitoring of automated manufacturing processes can provide competitive advantages for the company at a low cost.
Keywords: Computação móvel; Manufatura; Automação; Windows phone; Mobile computing; Manufacturing; Automation